COLLECTION OF MONEY OR GOODS: LEGAL CERTAINTY and STATE RESPONSIBILITY - Bango, Fikran S; Naswar; Sapiddin, Andi Syahwiah A. (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
This research aims to analyze the legal certainty of collecting money or goods in the midst of society, as well as what is the responsibility of the state that must be carried out in accordance with regulatory provisions. The type of research used is Normative Empirical legal research. The results obtained through literature studies and empirical data are then analyzed by the Normative Empirical method. The results showed that: 1). Legal certainty for the collection of money and goods in the community and the responsibility of the state which is tasked with overseeing the development of the collection of money and goods in Indonesia. 2) The fact of the development of philanthropic institutions in Indonesia is reviewed in the concept of philanthropy in Indonesia. Then the process of collecting money and goods must be in line with regulations.